A real-time approach of diagnosing rice leaf disease using deep learning-based faster R-CNN framework - Bari, Bifta Sama; Islam, Md Nahidul; Rashid, Mamunur; Hasan, Md Jahid; Mohd Azraai, Mohd Razman; Musa, Rabiu Muazu; Ahmad Fakhri, Ab. Nasir; Majeed, Anwar P.P. Abdul (PeerJ Inc., 2021)
The rice leaves related diseases often pose threats to the sustainable production of rice affecting many farmers around the world. Early diagnosis and appropriate remedy of the rice leaf infection is crucial in facilitating healthy growth of the rice plants to ensure adequate supply and food security to the rapidly increasing population. Therefore, machine-driven disease diagnosis systems could mitigate the limitations of the conventional methods for leaf disease diagnosis techniques that is often time-consuming, inaccurate, and expensive. Nowadays, computer-assisted rice leaf disease diagnosis systems are becoming very popular. However, several limitations ranging from strong image backgrounds, vague symptoms’ edge, dissimilarity in the image capturing weather, lack of real ﬁeld rice leaf image data, variation in symptoms from the same infection, multiple infections producing similar symptoms, and lack of efﬁcient real-time system mar the efﬁcacy of the system and its usage. To mitigate the aforesaid problems, a faster region-based convolutional neural network (Faster R-CNN) was employed for the real-time detection of rice leaf diseases in the present research. The Faster R-CNN algorithm introduces advanced RPN architecture that addresses the object location very precisely to generate candidate regions. The robustness of the Faster R-CNN model is enhanced by training the model with publicly available online and own real-ﬁeld rice leaf datasets. The proposed deep-learning-based approach was observed to be effective in the automatic diagnosis of three discriminative rice leaf diseases including rice blast, brown spot, and hispa with an accuracy of 98.09%, 98.85%, and 99.17% respectively. Moreover, the model was able to identify a healthy rice leaf with an accuracy of 99.25%. The results obtained herein demonstrated that the Faster R-CNN model offers a high-performing rice leaf infection identiﬁcation system that could diagnose the most common rice diseases more precisely in real-time.